Solo Supermom: Psychological Well-Being pada Ibu Tunggal yang Kehilangan Pasangan Meninggal Dunia - Sukmana, Hafiza Putri; Hanami, Yuliana (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2023)
A single mother who lost her spouse due to death bears the dual responsibility of being both a father and mother in the family, including managing the household, educating her children, and supporting herself. This situation places significant physical and mental pressure on her. The spouse’s role as a support system is no longer available to the single mom, and the grief experienced as an independent single mom leads to changes in her psychological well-being. This research aims to provide an overview of the psychological well-being of single mothers who have lost their spouses due to death. The study employs a descriptive qualitative approach with thematic analysis. Data collection involves semi-structured interviews with three participants using snowball sampling. The research findings indicate that single mothers undergo changes in self-acceptance and their current experiences after experiencing profound grief due to abandonment for approximately one year. Social support from the family influences a positive connection with their environment, while a lack of social support results in loneliness and reduced self-esteem. Job instability makes it difficult for single mothers to earn a living and be self-reliant. Social pressures related to the assessment of their status as widows and single mothers are felt by them. Single mothers have life goals related to the future of their children, and for those who are pessimistic, life is often entirely dedicated to their children, with limited opportunities for self-development. This research can be used by mental health promotion program designers and policymakers as additional empirical information on the current condition of single mothers' psychological well-being.